2007
DOI: 10.1177/0961463x07074103
|View full text |Cite
|
Sign up to set email alerts
|

No Time to Think

Abstract: This article reports on a study of how Canadian academics use on-line technologies to deal with increasing demands and time pressures. The results suggest that, in struggling to manage conflicting organizational and temporal priorities, academics are adopting practices to manage these conflicts which adversely affect the quality and content of their teaching and research. Moreover, these changes in practice are integral to reconstituting the temporal and organizational order of universities so they can functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(35 citation statements)
references
References 14 publications
0
22
0
2
Order By: Relevance
“…I'm working in an area where technology is moving quite fast…. It takes time to invest in new Time, well-known to be a precious commodity to academics (Ito and Brotheridge 2007;Menzies and Newson 2007;Ylijoki and Mantyla 2003), is what the CRC makes possible. The freedom to engage with students and collaborators, the opportunity to stay on top of one's research, and to build a research program are significant advantages that several CRCs identified as benefits of being a Chair.…”
Section: The Resultsmentioning
confidence: 98%
“…I'm working in an area where technology is moving quite fast…. It takes time to invest in new Time, well-known to be a precious commodity to academics (Ito and Brotheridge 2007;Menzies and Newson 2007;Ylijoki and Mantyla 2003), is what the CRC makes possible. The freedom to engage with students and collaborators, the opportunity to stay on top of one's research, and to build a research program are significant advantages that several CRCs identified as benefits of being a Chair.…”
Section: The Resultsmentioning
confidence: 98%
“…Other academics have perceived that social media usage might shift their attention from knowledge creation to knowledge production. For instance, the sample of academics included in the study by Menzies and Newson (2007) believed that being connected to social media on a 24/7 basis would limit their ability to think deeply about their work and, therefore, decrease their creativity. In addition, researchers who are convinced of the benefits of social media usage have complained that they lack sufficient time to do so (Rowlands et al, 2011).…”
Section: Social Mediamentioning
confidence: 99%
“…McAlpine and Amundsen (2009) reported that students were intentional in developing and drawing on a range of rewarding academic and non-academic relationships beyond the department in order to achieve personal goals. How an individual's networking strand is seen and the efforts made to develop it in light of such intentions are situated in, for instance, technologies that enable more contact with greater numbers of spatially separate individuals (Menzies and Newson 2007).…”
Section: Exploring the Notion Of Identity-trajectorymentioning
confidence: 99%